The Application of Information Technology in Distance Learning at Universitas Terbuka - Lisda Ariani Simabur; Tuti Bahfiarti; Muliadi Mau (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to analyze the application of Information and Communication Technology (ICT) in distance learning at Universitas Terbuka (UT), with a particular focus on how ICT supports accessibility, flexibility, and learning quality, especially in 3T (remote, frontier, and disadvantaged) areas. The research used a qualitative case study approach conducted over three months, involving 20 participants consisting of students, lecturers, system administrators, and librarians. Data were collected through in-depth interviews, non-participatory observations, and documentation. The results show that Universitas Terbuka has effectively integrated various digital platforms, including MyUT, e-Campus, online tutorials, and digital libraries, enabling students to access academic services independently and flexibly. Online tutorials, webinars, and distance learning workshops have also helped strengthen student engagement and self-directed learning. However, the study found that limited internet connectivity and low ICT literacy remain major challenges in 3T regions, affecting participation and learning outcomes. The study concludes that while ICT integration significantly enhances the accessibility and flexibility of distance education at Universitas Terbuka, its overall success depends on the availability of stable digital infrastructure and continuous improvement of users’ technological competence. These findings highlight the importance of government and institutional collaboration in expanding digital access to ensure equitable distance learning opportunities across Indonesia.